2021
DOI: 10.1108/ijchm-07-2021-0858
|View full text |Cite
|
Sign up to set email alerts
|

The effects of on-the-job embeddedness and its sub-dimensions on small-sized hotel employees’ organizational commitment, work engagement and turnover intentions

Abstract: Purpose This paper aims to examine the impacts of links, fit and sacrifice as the sub-dimensions of on-the-job embeddedness (JE) on turnover intentions through the mediating roles of affective organizational commitment (AOC) and work engagement (WENG) and explore AOC and WENG as the two mediators linking on-the-JE to quitting intentions. Design/methodology/approach Data collected from small-sized hotels in three waves in Ghana were used to assess the aforesaid relationships. The hypothesized relationships we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
6

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 83 publications
(124 reference statements)
2
48
0
6
Order By: Relevance
“…Findings of the studies carried out during the pandemic also point out that employees’ levels of TI decrease as their levels of OC increase. The findings of the studies by Ampofo and Karatepe [ 34 ] in Ghana, Tsaousoglou et al [ 36 ] in Greece, Murray and Holmes [ 35 ] in Canada, and Yan et al [ 93 ] in Chinese hotel employees correlate with the findings of this study. OC is a variable that is intricately linked with TI [ 165 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Findings of the studies carried out during the pandemic also point out that employees’ levels of TI decrease as their levels of OC increase. The findings of the studies by Ampofo and Karatepe [ 34 ] in Ghana, Tsaousoglou et al [ 36 ] in Greece, Murray and Holmes [ 35 ] in Canada, and Yan et al [ 93 ] in Chinese hotel employees correlate with the findings of this study. OC is a variable that is intricately linked with TI [ 165 ].…”
Section: Discussionsupporting
confidence: 89%
“…We believe that providing support to employees in the tourism sector who have been adversely affected by the pandemic, reducing their TI, and increasing their organizational commitment (OC) will provide various advantages. Numerous studies in the literature regarding the pandemic revealed remarkable results such as OS increasing OC [ 29 , 30 , 31 ], and OS [ 24 , 32 , 33 ] and OC [ 34 , 35 , 36 ] decreasing TI. Still, we believe that examining the links between OS, OC, and TI in detail and in relation with employees’ infection status and perceived JI is also very important, because the perceived OS, level of OC, and TI of employees, who were infected during the pandemic, will differ from those who were not infected, despite the direct exposure of both groups to the crisis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations